The Relationship Between Breakfast and Tea Drinking Habits with the Incidence of Anemia in Adolescent Girls in the Randublatung Health Center Working Area: Hubungan antara Kebiasaan Sarapan dan Minum Teh dengan Kejadian Anemia pada Remaja Putri di Wilayah Kerja Puskesmas Randublatung - Mayasari, Ovita (Politeknik Assalaam Surakarta, 2025)
Anemia is a condition where the hemoglobin level in red blood cells (erythrocytes) decreases, impairing the ability of red blood cells to carry oxygen throughout the body. Adolescent girls are more susceptible to anemia due to the increased iron requirements for supporting growth and the menstrual cycle. According to the World Health Organization (WHO), the prevalence of anemia among adolescent girls worldwide remains relatively high (40-80%), with anemia in Indonesia among 15-24 years old at 15.5%. In Central Java, the prevalence of anemia is 48.9%, while the anemia rate among adolescent girls in the working area of Puskesmas Randublatung is recorded at 41.14%. This studey aims to determine the relationship beetween breakfast habits and tea consumption with the occurence of anemia in adolescent girls in the Puskesmas Randublatung working area. The research used a quantitative method with a cross-sectional design. The sampling technique used was Simple Random Sampling, and data analysis was conducted using the Chi-Square Test. The results showed a relationship between breakfast habits and tea consumptoion with the incidence of anemia among adolescent girls in the Puskesmas Randublatung working area. These findings can provide input for relevant institutions to offer education on anemia prevention, such as encouraging breakfast habits and reducing tea consumption during meals for adolescent girls.